Bilinbox: A Solar-Powered Smart Home Parcel Receiver Box - Raymart O Poras; Alyssa T Infantado; Ceza Jean O Sending; Jaydel M Vapor; Jesabell T Vapor; Warnner Daminar Amin; Warnner Daminar Amin (Universitas Multi Data Palembang, 2026)
The rapid growth of online shopping has led to an increase in parcel deliveries, causing recurring problems such as missed deliveries and inefficiencies in last-mile logistics, especially when recipients are not at home. This study developed BilinBox, a solar-powered smart home parcel receiver designed to ensure safe, convenient, and sustainable parcel handling. BilinBox integrates secure authentication using RFID and QR code scanning, automated locking mechanisms, IoT connectivity, and real-time monitoring, while promoting sustainability through solar energy use, supporting SDG 7, 9, 11, and 12. Its performance and software quality were evaluated using ISO/IEC 25010 standards through structured questionnaires administered to twenty (20) online shoppers and five (5) delivery riders. Results showed that online shoppers rated the system with an overall mean of 4.825 (“Excellent”), while delivery riders rated most criteria 5.0 (“Excellent”), with portability receiving 4.71, yielding an overall weighted mean of 4.825 (“Excellent”). These findings demonstrate that BilinBox is effective, reliable, and user-friendly, providing a secure and efficient solution for last-mile parcel delivery. Recommendations for further improvement include increasing box capacity, enhancing solar charging efficiency, enabling full remote monitoring, and integrating payment features for added convenience.